In vitro impact of platinum nanoparticles on inner ear related cell culture models - Berger, Elisabeth; Brandes, Gudrun; Reifenrath, Janin; Lenarz, Thomas; Durisin, Martin; Wissel, Kirsten (PLOS ONE, 2023)
So far, it was supposed that the increase of electrical impedance following cochlear implant (CI) insertion was due to technical defects of the electrode, inflammatory and/or formation of scar tissue along the electrode. However, it was recently reported that corrosion of the platinum electrode contacts may be the reason for high impedances. It could be shown that platinum particles were stripped from the electrode surfaces. Its potential cytotoxic effects within the inner ear remains to be examined. In this study in vitro cell culture models of the mouse organ of Corti cell line (HEI-OC1) and the spiral ganglion (SG) cells derived from the cochleae neonatal rats were used to investigate the effects of the polyvinylpyrrolidone coated platinum nanoparticles (Pt-NPPVP, 3 nm) on cell metabolism, neuronal survival and neurite outgrowth. Our data revealed no decrease of the metabolic activity of the HEI-OC1 cells at Pt-NPPVP concentrations between 50–150 μg/ml. Also, staining with Calcein AM/EthD demonstrated prevalent presence of vital cells. As shown by transmission electron microscopy no Pt-NPPVP could be found at the cell surface or in the cytosol of the HEI-OC1 cells. Similarly, the SG cells exposed to 20–100 μg/ml Pt-NPPVP did not show any reduced survival rate and neurite outgrowth following staining of the neurofilament antigen even at the highest Pt-NPPVP concentration. Although the SG cells were exposed to Pt-NPPVP for further 72 h and 96 h immunocytochemical staining of the glial cells and fibroblasts presented normal cell morphology and growth independently of the cultivation period. Our data indicates that the used Pt-NPPVP do not trigger the cellular uptake and, thus, presumable do not initiate apoptotic pathways in cells of the organ of Corti cell line or the auditory nerve. The protection mechanisms to the Pt-NPPVP interactions remain to be clarified.